2018
DOI: 10.31580/apss.v2i2.364
|View full text |Cite
|
Sign up to set email alerts
|

Sell in May and Go Away in Small & Big Companies on Indonesia Stock Exchange

Abstract: The study was conducted to prove the occurrence of market abnormalities phenomena, namely, sell in May and go away on the Indonesian Stock Exchange (IDX). By distinguishing stocks based on their size from stock prices as indicators, it is expected to see more accurate results in revealing this phenomenon. The hypothesis in this study is that there are differences in stock returns in May-October and November-April. The results of the study prove that there are no differences in stock returns in May-October and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In these anomalies, something is found that should not happen if the market is truly efficient. (Hayati & Jamil, 2018) define anomaly as a situation where the stock return of a company does not match the expected value, namely when the average financial performance of all companies is good, the return should increase.…”
Section: Figure 1 Development Of the Number Of Investors In The Indon...mentioning
confidence: 99%
“…In these anomalies, something is found that should not happen if the market is truly efficient. (Hayati & Jamil, 2018) define anomaly as a situation where the stock return of a company does not match the expected value, namely when the average financial performance of all companies is good, the return should increase.…”
Section: Figure 1 Development Of the Number Of Investors In The Indon...mentioning
confidence: 99%